Epidemiological and clinical profile of adult patients with diarrhoea after international travel attended in an International Health referral center. Issue 45 (January 2022) - España-Cueto, Sergio; Salvador, Fernando; Oliveira, Inés; Goterris, Lidia; Treviño, Begoña; Sánchez-Montalvá, Adrián; Serre-Delcor, Núria; Sulleiro, Elena; Rodríguez, Virginia; Aznar, María Luisa; Bosch-Nicolau, Pau; Espinosa-Pereiro, Juan; et al.
Abstract: Background: The aim of the study is to describe the epidemiological, clinical, and microbiological characteristics of patients with diarrhoea after their return from a trip to tropical and subtropical areas. Methods: Retrospective study of patients with travel-related diarrhoea attended International Health referral center. Travel diarrhoea was defined as the presence of three or more liquid stools per day, or liquid stools more often than is normal for the individual, during travel or within two weeks after returning. Epidemiological, clinical and microbiological variables were collected. Results: 669 patients were included, 393 (58.7%) were female, with a mean age of 33 (SD 10.7) years. Abdominal pain was present in 59.6% (n = 399), and fever in 44.7% (n = 299). In 43% (n = 280) cases the etiological agent was found. Giardia duodenalis, Enteropathogenic Escherichia coli, and Enterotoxigenic Escherichia coli were the most frequent identified causative agents. Parasitic cause of the diarrhoea was associated to a longer duration of the travel, longer duration of symptoms, and having received pre-travel counseling. Conclusions: In our cohort, that represents a group of travellers presenting prolonged symptoms after travel, the most frequent causes of diarrhoea were parasitic infections being the most prevalent Giardia duodenalis . This information could be relevant in order to improve travel-related diarrhoea management protocols in this type of patients.